The role of psychosocial training in increasing adaptive coping mechanisms in women survivors of violence - Yaroslava Popovych; Hanna Pavlenko; Hanna Voshkolup; Yevhen Potapchuk; Zinaida Antonova (Revista Cubana de Medicina Militar)
Introduction: The relevance of the research is determined by the study of the effectiveness of psychosocial interventions for women’s ability to find new ways to overcome stress caused by violence.